Mental Health Issues and the University Student - Iarovici, Doris (Book collections on Project MUSE., 2014)
"Dr. Iarovici describes the current college mental health crisis and narrates how college mental health services have evolved along with changes in student populations. She discusses students' lifestyle problems and psychiatric concerns, using case vignettes to explore a variety of interventions. Included are discussions of substance abuse, relationship difficulties, eating disorders, depression and anxiety, and culture clashes. Problems uniquely addressed in this book include sleep disturbances and perfectionism. An essential component of the volume is a guide to making emergency assessments, from risk classification and hospitalization to public safety and communication within and outside the campus community."--Publisher's website